The socioeconomic determinants of crime : the case of Texas - Balthazar, Kristin Ross (2012)
This paper investigates the relationship between various socioeconomic factors and crime, especially income inequality and poverty. As crime rates have steadily increased over time, ecological theories of crime have been developed to explain the behavior of both property crime and violent crime. Identifying possible predictors of crime is one step into developing social policies that will help lower the vast social costs of criminal activity. The first part of this paper discusses the three major ecological theories thought to best explain crime (strain theory, social disorganization theory, and economic theory). The second part uses county-level data from the state of Texas to explore the links between likely socioeconomic factors and crime rates. Our analysis provides evidence that inequality is unlikely to be a constantly significant factor in determining property crime rates but does have a significant impact on violent crime. Family instability is the most consistently significant determinant of both types of crime